The influence of market orientation and new product development processes on new product success - Martínez-Lobatón, Jorge (2025)
Since not all new products are introduced to the market successfully, the quality of the new product development process and its technical or market focus are of special importance. Many studies based on large companies in developed economies show that market orientation is a key factor for success. Despite this, little attention is still paid to this issue in developing economies. The purpose of this study is to analyze to what extent the success of new products depends on the rigor with which new product development processes are carried out and their market orientation. Using a dendrogram with the Ward’s linkage method on a sample of 140 manufacturing companies from Peru, three clusters of companies were identified. The clusters that report the greatest success are those characterized by superior quality and a strong technical orientation.